Plato's Gorgias - Labyrinth and Threads - Tomaz Fidalgo (Outros titulos, 2020)
Though at first it may seem to deal with rather specific questions concerning rhetoric, Plato's Gorgias turns out to be about human life, and what is at stake in it. This apparent "change of subject" - or rather this ambiguity in the dialogue's subjectmatter - has to do with the fact that the Gorgias is very much like a labyrinth: puzzling, intricate, made of multiple meandering paths in which one can easily get lost, and full of deviations which turn this way and that, of entrances that seem to be dead ends, and of dizzying turns that distort all sense of direction.